Crenarchaeal heterotrophy in salt marsh sediments - Seyler, Lauren M (Nature Publishing Group, 2014)
Mesophilic Crenarchaeota (also known as Thaumarchaeota) are ubiquitous and abundant in marine habitats. However, very little is known about their metabolic function in situ. In this study, salt marsh sediments from New Jersey were screened via stable isotope probing (SIP) for heterotrophy by amending with a single (13)C-labeled compound (acetate, glycine or urea) or a complex (13)C-biopolymer (lipids, proteins or growth medium (ISOGRO)). SIP incubations were done at two substrate concentrations (30–150 μM; 2–10 mg ml(−1)), and (13)C-labeled DNA was analyzed by terminal restriction fragment length polymorphism (TRFLP) analysis of 16S rRNA genes. To test for autotrophy, an amendment with (13)C-bicarbonate was also performed. Our SIP analyses indicate salt marsh crenarchaea are heterotrophic, double within 2–3 days and often compete with heterotrophic bacteria for the same organic substrates. A clone library of (13)C-amplicons was screened to find matches to the (13)C-TRFLP peaks, with seven members of the Miscellaneous Crenarchaeal Group and seven members from the Marine Group 1.a Crenarchaeota being discerned. Some of these crenarchaea displayed a preference for particular carbon sources, whereas others incorporated nearly every (13)C-substrate provided. The data suggest salt marshes may be an excellent model system for studying crenarchaeal metabolic capabilities and can provide information on the competition between crenarchaea and other microbial groups to improve our understanding of microbial ecology.